Deep Learning for Spectroscopic X‐ray Nano‐Imaging Denoising - Tianyu Fu; Kai Zhang; Qingxi Yuan; Jizhou Li; Piero Pianetta; Yijin Liu (Advanced Intelligent Systems)
Synchrotron transmission X‐ray microscopy with absorption near edge structure (TXM‐XANES) is a powerful tool for investigating the structure and composition of materials at nano‐ to meso‐scales. It is, however, often challenged by high levels of noise that obscure critical details at the single‐pixel level. To address this issue, a deep learning‐based algorithm is developed for suppressing the image noise, grounded in self‐supervised learning principles. In contrast to traditional image denoising methods, this approach successfully enhances the visibility of fine details while significantly reducing the noise in the X‐ray images. Through this advancement, the potential of the approach for improving the accuracy and interpretability of the TXM‐XANES data is demonstrated, thereby enabling more precise detection of nanoscale phenomena such as inhomogeneous cation redox and metal segregation in battery cathode materials. This technique offers an effective new avenue for harnessing the full potential of synchrotron TXM‐XANES imaging, paving the way for a range of exciting new studies in materials science and beyond.